Crescimento de genótipos de pitaieira em diferentes sistemas de condução e conservação de pitaias minimamente processadas (corte, embalagem e tempos de conservação) - Martins, Lilian Aparecida (2024)
The pitaya plant, as it is still an up-and-coming crop in Brazil, studies related to its management in the field and the post-harvest of its fruit are necessary. The aim of this study was to evaluate the growth of pitaya plant of six genotypes in three handling systems, as well as to examine the influence of different cuts and packaging on the storage of white-fleshed pitaya. The work was divided into two experiments. The first experiment was carried out at Unioeste's Experimental Farm, using a randomized block design in a 6 x 3 factorial scheme (pitaya plant genotypes x handling systems), with one plant per experimental unit and three replications. The following pitaya plant were tested: Lua do Cerrado, Vietnamese White, Palora, Halleys Commet, Golden and Orejona. The seedlings were planted using the rubber ring, trellis and espalier systems. The phytotechnical evaluations began in June 2023 and continued every three months until they completed the one-year cycle. During the evaluations, plant height (m) was analyzed, the number of cladodes above the trellis, the number of lateral cladodes and the absolute growth rate of the plant were calculated. The second experiment was conducted at Unioeste's PostHarvest Technology Laboratory in February 2024, using a completely randomized design in a 2 x 3 x 5 factorial scheme (cuts x packaging x storage times), with two replications and two samples per replication. Fruit flesh and skin color (L*a*b), loss of fresh biomass (g), flesh firmness (N), pH and soluble solids (ºBrix) were evaluated. In the first experiment, the greatest vegetative development of the pitaya plant occurred between June and September, with the rubber ring and espalier systems being the best for cultivation. The Halleys Commet, Lua do Cerrado and Golden genotypes showed the best canopy formation and production potential. In the second experiment, during storage, the color of the pulp and peel increased, while the firmness decreased. The polystyrene tray covered with polyvinyl chloride film and the rectangular polypropylene packaging provided better fruit preservation, with the 1/2 cut with peel being the best option for marketing.